Microstructure evolution and mechanical properties of selective laser melted bulk-form titanium matrix nanocomposites with minor B4C additions. (5th January 2020) - Li, Hailiang; Yang, Zhihua; Cai, Delong; Jia, Dechang; Zhou, Yu
Abstract: Crack-free and almost fully dense (≥99%) bulk-form titanium matrix nanocomposites in-situ synthesized from a ball-milled mixture of Ti-6Al-4V and B4 C powders were achieved through an optimized selective laser melting (SLM) process. The effects of minor B4 C addition on microstructure evolution, hardness, compressive properties and fracture mechanisms of the composites were systematically investigated. The in-situ synthesized nanoscale TiBw or TiCp ceramic reinforcements, exhibiting a quasi-continuous (TMC1) or full-continuous structure (TMC2), could play a prominent role in determining the microstructure refinement and mechanical properties of the composites. Results indicate that the SLM-processed nanocomposites exhibit a maximum increase of 45% of Vickers microhardness and 26% of ultimate compressive strength over the Ti-64 alloy. The enhancement of mechanical properties is mainly attributed to the second-phase strengthening, grain refinement strengthening as well as solid solution strengthening induced by the interstitial carbon in Ti matrix. This study provides a novel solution for microstructure tailoring with minor B4 C addition and producing high-performance titanium matrix composites via SLM additive manufacturing. Graphical abstract: Image 1 Highlights: Crack-free bulk-form titanium matrix nanocomposites with relative density ≥99% were fabricated by selective laser melting. In-situ synthesized nanoscale TiB whiskers or TiC particles distributed in the titanium matrix were achieved. The composites evolve from quasi-continuous to full-continuous wall-like or network structure with increasing B4 C content. The composites show a maximum increase of 45% of Vickers microhardness and 26% of compressive strength over the Ti-64.